CREDIT DERIVATIVE AND ITS USE IN THE BANKING INDUSTRY - Nagda, Deshna (2008)
The credit derivative market has emerged as one of the most dynamic and innovative sectors of the global financial system, so now the credit derivatives are generating a lot of interest within the financial community. Simply put, credit derivative contracts are financial instruments that transfer between two parties the risk and return characteristics of a credit-risky reference asset. As with other derivatives, credit derivative can be used to either take more risk or hedge it; hence various credit derivatives instruments are accepted and widely used by market participants such as banks, insurance companies, etc. This paper aims to provide a general insight into the use of credit derivative in banking industry.